2013
DOI: 10.1097/fpc.0b013e3283647c33
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the Taq1A variant in the dopamine D2 receptor gene and common CYP2D6 alleles on prolactin levels in risperidone-treated boys

Abstract: Although CYP2D6 might have an effect, the presence of at least one Taq1A A1 allele of the D2DR gene did not contribute toward susceptibility to risperidone-induced hyperprolactinemia, and as a result, toward prolactin-related adverse events such as amenorrhea, galactorrhea, and sexual dysfunctioning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 42 publications
2
39
1
Order By: Relevance
“…A study by Roke et al [25] aimed to better understand the hyperprolactinemia associated with risperidone use, which affects 50 % of children on long-term treatment. Based on the role of dopamine 2 antagonism and association between the A1 allele of the dopamine D2 receptor (DRD2) Taq1A polymorphism in adults, the authors investigated whether variation in the DRD2 gene may modify the effects of risperidone on prolactin levels.…”
Section: Atypical Antipsychoticsmentioning
confidence: 99%
“…A study by Roke et al [25] aimed to better understand the hyperprolactinemia associated with risperidone use, which affects 50 % of children on long-term treatment. Based on the role of dopamine 2 antagonism and association between the A1 allele of the dopamine D2 receptor (DRD2) Taq1A polymorphism in adults, the authors investigated whether variation in the DRD2 gene may modify the effects of risperidone on prolactin levels.…”
Section: Atypical Antipsychoticsmentioning
confidence: 99%
“…It should also be noted that lower doses could also cause serious adverse events [29]. It is important to keep in mind that hyperprolactinaemia may be present without these adverse events [13,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Elevation of prolactin concentration corresponds to dopamine D2 receptor blockade [9,10]. Most studies report that children and adolescents treated with risperidone have 38-50% incidence of hyperprolactinaemia [4,[11][12][13][14][15][16].Early studies reported adverse effects associated with prolactin elevation because hyperprolactinaemia is one of the most common endocrinological disorders of the hypothalamic-pituitary axis [8]. Hyperprolactinaemia in female patients can result in amenorrhoea, galactorrhoea, anovulation and irregular menses, and in male patients, it can lead to azoospermia, impotence, gynaecomastia and galactorrhoea [17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A well-known side effect associated with risperidone is the elevation of prolactin levels. 1 This elevation occurs because risperidone antagonizes D2 receptors on lactotroph cells of the anterior pituitary gland, which serves a main inhibitory role in prolactin secretion. Risperidone causes higher levels of prolactin elevation compared to other atypical antipsychotics.…”
mentioning
confidence: 99%